Compound‐specific amino acid δ15N values in archaeological shell: Assessing diagenetic integrity and potential for isotopic baseline reconstruction. (11th October 2017) - Misarti, Nicole; Gier, Elizabeth; Finney, Bruce; Barnes, Kelli; McCarthy, Matthew
Abstract : Rationale: Reconstructing stable isotope (SI) ratios at the base of paleo‐food webs is often challenging. For coastal systems, the SI ratios of organic matter in archeological shell represents a possible solution, providing a direct record of primary consumer SI ratios in the littoral zone. However, shell is often porous, with organic compounds susceptible to diagenetic alteration or contamination. If molecular isotopic information is well preserved, compound‐specific amino acid isotope analysis (CSI‐AA) has the potential to provide direct proxies for baseline SI ratios, bypassing many contamination issues, and to allow assessment of the diagenetic state. Methods: We collected shell from both archeological middens and nearby littoral zones in coastal Alaska, and used a simple organic extraction approach based on decalcification with sequential weak HCl additions to liberate organic material. We measured CSI‐AA patterns, molar AA distributions, and the CSI‐AA degradation parameter (ΣV), in the context of bulk SI ratios in fossil shell, modern shell, and soft tissue from five common taxa (urchin, limpet, mussel, periwinkle, chiton). Results: CSI‐AA patterns in both soft tissue and shell were consistent with primary consumers, and were indistinguishable in most modern and fossil shell pairs, showing that amino acid δ 15 N values can be well preserved in archeological shell. AA molar distributions were also similar, although most fossil shell was enriched in Asx and Gly. Comparison between CSI‐AA results from modern specimens confirmed that the source AA group (tracking isotopic baselines) are transferred without substantial modification into the shell record. In contrast, the Trophic AA group had elevated δ 15 N values in shell versus soft tissue for all taxa examined, suggesting that a correction factor will be required for any CSI‐AA proxies using these AAs. Conclusions: Overall, this new data indicates that the CSI‐AA analysis of fossil shell represents a promising new approach to determining isotopic baselines in coastal paleo‐ecosystems.